2019
DOI: 10.3390/ijms20051247
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Editing of the Nuclear APT Reporter Gene in Chlamydomonas reinhardtii via Expression of a CRISPR-Cas9 Module

Abstract: The clustered regularly interspaced short palindromic repeat/CRISPR-associated protein 9 (CRISPR/Cas9) technology is a versatile and useful tool to perform genome editing in different organisms ranging from bacteria and yeast to plants and mammalian cells. For a couple of years, it was believed that the system was inefficient and toxic in the alga Chlamydomonas reinhardtii. However, recently the system has been successfully implemented in this model organism, albeit relying mostly on the electroporation of rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…Recently, some reports suggested that gene selection can be achieved with high yields (up to 30%) through counter selection without the use of antibiotic genes (Jiang and Weeks, 2017;Serif et al, 2018;Guzmán-Zapata et al, 2019). However, these methods are mostly functional for specific genes and cannot be applied universally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some reports suggested that gene selection can be achieved with high yields (up to 30%) through counter selection without the use of antibiotic genes (Jiang and Weeks, 2017;Serif et al, 2018;Guzmán-Zapata et al, 2019). However, these methods are mostly functional for specific genes and cannot be applied universally.…”
Section: Discussionmentioning
confidence: 99%
“…crRNA and tracrRNA can be physically linked to form single guide RNA (gRNA) (Jinek et al, 2012). In C. reinhardtii, the CRISPR-Cas9 was first applied via DNA vector system in 2014 and recently ribonucleoprotein (RNP) system has been developed (Jiang et al, 2014;Baek et al, 2016;Guzmán-Zapata et al, 2019). CRISPR-Cas9 system is the ideal tool for gene-editing; however, it requires efficient selective markers for reducing the time and labor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raised concerns that Cas9 was toxic in C. reinhardtii. More recent studies, exploring different approaches, have clearly demonstrated that CRISPR/Cas9 is useful for targeted disruption of genes in C. reinhardtii [15][16][17][18][19][20][21][22]. However, some of the published methods have low efficiencies of achieving the desired edit, making it laborious to identify cells in which a gene has been successfully targeted, especially in the absence of a selectable marker.…”
Section: Introductionmentioning
confidence: 99%
“…Although technology for precision genome editing, including zinc-finger nucleases, transcription activator-like effector nucleases (TALENs), or CRISPR/Cas9, has been reported in many microalgae (Sizova et al, 2013;Weyman et al, 2015;Li et al, 2016;Nymark et al, 2016;Ajjawi et al, 2017), several challenges related to targeting, efficiency, and toxicity remain to be fully overcome. Strategies to circumvent these issues include transient Cas9 expression (Guzmán-Zapata et al, 2019), direct ribonucleoprotein (RNP) delivery (Baek et al, 2016;Shin et al, 2016) and use of Cas variants (Ungerer and Pakrasi, 2016). Marker-free and multiplex gene knock-out remains a challenge in some microalgae, although the use of multiple sgRNAs to multiplex genome editing targets has been shown to be feasible in diatoms (Serif et al, 2018).…”
Section: Synthetic Biologymentioning
confidence: 99%